Розроблення електронного каталогу в додатку Android для продажу товарів мережі магазинів “Свій Маркет” - Кулічкова, Мар’яна; Мина, Жанна (Видавництво Львівської політехніки, 2020)
Theses highlight the importance of the impact and development of information technology on the activities of commercial enterprises. After all, with the development of the Internet market, it is necessary to look for new opportunities to present their products or activities on the Internet. It is emphasized the importance of cooperating with customers and the ability to present the product profitably and convince the buyer to buy it. A comparative analysis of applications and the conclusion of which application will be used.
Keywords: каталог; додаток для Android; Інтернет; клієнт; маркетинг; мобільна реклама